(untitled) (Journal of Engineering, 2006)
Because of practical importance of protecting industrial equipments from galvanic corrosion, the need arises to analyze the effects of variables, such as temperature, velocity, and area fraction of metals on galvanic corrosion in systems under mass transfer control as in seawater (pH=7). For these reasons the galvanic corrosion of Fe-Zn is analyzed to study the influence of Reynolds number, temperature, and area fraction on the galvanic corrosion rates and galvanic corrosion potential under mass transfer control. It is found that galvanic corrosion rate of more active metal (Zn) is increased with Reynolds number while the corrosion rate of more noble metal (Fe) is slightly increased with Re depending on the galvanic potential that depends on the area fraction. Increasing Reynolds number shifts the galvanic potential to more positive values. Also increasing temperature leads to shift the corrosion potential to more negative values and to change the corrosion rate of more active metal (Zn) depending on two parameters oxygen solubility and oxygen diffusivity. As area fraction of more active metal (Zn) increased the galvanic potential is shifted to the negative anodic direction while the corrosion rate for more noble metal is decreased.